Pengaruh Terapi Akupresur Mandiri terhadap Gangguan Kecemasan dan Keluhan Menopause: Effect of Self-Acupressure Therapy on Anxiety Disorders and Menopausal Complaints - Mulyandari, Ani; Trisnawati, Yeti (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
Menopause is something that cannot be avoided, especially in women, as an aging process. This condition will cause various kinds of disorders, both physical and psychological, which will have a negative impact, both short and long-term, especially on the quality of life and physical and mental health of women. Complaints that many menopausal women feel are a decrease in physical function and complaints of anxiety. It is believed that acupressure therapy can be a straightforward alternative for every individual to reduce both physical and psychological complaints in women. This research aimed to prove the effect of independent acupressure therapy on reducing anxiety levels and menopausal complaints in mothers. The research used a quasi-experimental pre - and post-test design approach in the case and control groups, with treatment in the case group as acupressure therapy with the fingers. The research respondents were 32 menopausal mothers aged 45 - 60 using purposive sampling. An elderly Posyandu conducted this research in the Mekar Baru Community Health Center, Tanjungpinang City. Data analysis used an independent samples test and paired samples t-test. The research results showed that there was a decrease in the level of anxiety and menopausal complaints after the independent acupressure intervention with the fingers with a p-value <0.05. The recommendations of this research are the importance of independent acupressure intervention to overcome the problem of physical complaints and anxiety in menopausal women.